Veil of winter - Dickerson, Melanie (A Dericott tale, 2022)
In this retelling of the fairy tale Sleeping Beauty, Princess Elyce escapes unscrupulous King Conrad by taking a sleeping potion, and after Sir Gerard wakes her with a kiss they begin their journey to Prague in the dead of winter.